Integrating Reason, Logic, and Islamic Epistemology for Holistic Science in Modern Education - Nasir, Tatang Muh; Purnama, Wawan; Haryanti, Erni; Komara, Dadang; Sain, Zohaib Hassan (Atthulab: Islamic Religion Teaching and Learning Journal, 2025)
This study examines the role of reasoning, logic, and sources of knowledge in the development of modern science, focusing on how these concepts are understood and applied by students from both general and Islamic educational backgrounds. The research aims to explore the relationship between critical reasoning, logical processes, and knowledge sources in learning and daily life. Using a qualitative phenomenological design, data were collected through semi-structured interviews and analyzed thematically. The findings reveal that students employ both inductive and deductive reasoning to solve academic and everyday problems, with logic serving as a tool for constructing coherent conclusions. Knowledge sources include empirical experience, rational thinking, and guidance from religious teachings. The study concludes that reasoning, logic, and knowledge sources are interrelated and play a crucial role in shaping holistic science. Importantly, these insights highlight practical implications for contemporary education, suggesting that the integration of rational, empirical, and spiritual perspectives can inform curriculum design and pedagogy to foster deeper understanding, critical thinking, and character formation among student.